Interferon status at the women with recurrent genital herpes in combined liposomal RNA treatment - A. Sh. Makhmutkhodzhayev; I. D. Yevtushenko; S. N. Targonsky; C. V. Ussova; N. M. Dzhilkibayeva (Бюллетень сибирской медицины, 2012)
The aim of this study was the estimation of the influence of liposomal ribonucleic acid (RNA) medicine «Liprina» on interferon status of women with recurrent genital herpes. In this study 60 women were included, who combined (acyclovir and Liprina, n = 40) or monoterapy with acyclovir (n = 20) were received. The levels of serum interferon alpha and gamma along with cervical virus elimination were estimated. The medicine «Liprina» increased the therapy efficiency of the women with genital herpes, that perhaps related with endogen interferon production amplification.